2013
DOI: 10.4172/2327-5162.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Human and Poultry Use in the Control of Gastrointestinal Disease: A Review of Real-World Experiences

Abstract: Over a century ago Eli Metchnikoff proposed the revolutionary idea to consume viable bacteria to promote health by modulating the intestinal microflora. The idea is more applicable now than ever, since bacterial antimicrobial resistance has become a serious worldwide problem both in medical and agricultural fields. The interest in digestive physiology and the microbiome has generated data whereby well being of all living organisms with a digestive tract can be enhanced and the risk of disease reduced. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
1
0
0
Order By: Relevance
“…Several studies have reported different to prevent infections against foodborne pathogens [25,26,45]. In this report, we showed that L. t inflammatory foci at 4F and 4H).…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have reported different to prevent infections against foodborne pathogens [25,26,45]. In this report, we showed that L. t inflammatory foci at 4F and 4H).…”
Section: Discussionsupporting
confidence: 52%